2022
DOI: 10.1111/are.15808
|View full text |Cite
|
Sign up to set email alerts
|

Production and use of immunoglobulin Y in the diagnosis of haemorrhagic septicemia caused by Aeromonas hydrophila in Piaractus mesopotamicus

Abstract: Aeromonas hydrophila is an opportunistic pathogen frequently isolated from outbreaks with higher mortality rates in tropical farms, causing disease in pacus Piaractus mesopotamicus. The objective of this study was to obtain a purified polyclonal immunoglobulin Y (IgY) by immunizing laying White Leghorn hens with A. hydrophila. Antibodies anti‐A. hydrophila derived from the yolks and serum of hens showed antibody titres increased at 60 days and remained detectable until 90 days after immunization. Pacus were ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…The clinical symptoms in patients were obviously enhanced through a two-week dietary of anti-Hp IgY and Hp eradication reached 30.6%. Fernandes et al ( 2022 ) revealed that IgY possessed the capacity in detection of Aeromonas hydrophila in Piaractus mesopotamicus . The prophylactic potential of IgY against dental caries in humans and animals also has been studied (Sharma and Kaur, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…The clinical symptoms in patients were obviously enhanced through a two-week dietary of anti-Hp IgY and Hp eradication reached 30.6%. Fernandes et al ( 2022 ) revealed that IgY possessed the capacity in detection of Aeromonas hydrophila in Piaractus mesopotamicus . The prophylactic potential of IgY against dental caries in humans and animals also has been studied (Sharma and Kaur, 2019 ).…”
Section: Introductionmentioning
confidence: 99%